2019
DOI: 10.9734/jamps/2019/v21i330132
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Phytochemical Analysis and Antifungal Susceptibility of Vernonia amygdalina against Some Strains of Candida albicans

Abstract: This study was aimed at determining the quantitative phytochemical analysis and antifungal susceptibility of Vernonia amygdalina against some strains of Candida albicans. Reflux method of extraction was used for the successive extraction of the leaves of Vernonia amygdalina. Quantitative phytochemical screenings were done to determine the amounts of phytochemicals that are present in the crude extracts, the study revealed that phytochemicals which include flavonoids, tannins, alkaloids, saponins and phenol wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…This is in agreement with a previous report in which the aqueous, ethanolic, and methanolic extracts of Vernonia amygdalina did not elicit inhibitory activity against c. albicans [20]. On the other hand, the result contradicted a study in which it was found that methanol, n-hexane, and ethylacetate crude extracts of leaves of v. amygdalina elicited antifungal activity against Candida albicans [21]. This might be a result of bioactive substances in the leaves of v. amygdalina that have antifungal potential against c. albicans.…”
Section: Antimicrobial Activity Of the Vernonia Amygdalina Aqueous Le...supporting
confidence: 91%
“…This is in agreement with a previous report in which the aqueous, ethanolic, and methanolic extracts of Vernonia amygdalina did not elicit inhibitory activity against c. albicans [20]. On the other hand, the result contradicted a study in which it was found that methanol, n-hexane, and ethylacetate crude extracts of leaves of v. amygdalina elicited antifungal activity against Candida albicans [21]. This might be a result of bioactive substances in the leaves of v. amygdalina that have antifungal potential against c. albicans.…”
Section: Antimicrobial Activity Of the Vernonia Amygdalina Aqueous Le...supporting
confidence: 91%